The Puritan Family and Its Relevance for Christian Families in Jakarta: A Reflection on the Social Construction - Sugianto Sugianto (Journal of Religious and Socio-Cultural, 2025)
This study explores how the social construction of Puritan family values in New England, interpreted through Berger and Luckman’s social construction theory, can inspire Christian families in Jakarta to reinforce their spiritual and moral foundations. As Jakarta faces issues such as domestic violence and family neglect, there is an urgent need for family structures that support resilience, moral development, and social cohesion. By examining the dialectical process of externalization, objectivation, and internalization, this research illustrates how Puritan values—integrated into daily family life—could serve as a model for Jakarta. The Puritan family was more than a social unit; it was a ‘mini-church’ where each member contributed to mutual spiritual growth and moral discipline. Adapting these principles, Christian families in Jakarta can strengthen their spirituality despite urban pressures by prioritizing communal worship, modeling ethical behavior, and leveraging technology for spiritual practices. The findings suggest that families with a strong spiritual foundation are better equipped to serve as positive influences within their communities, offering integrity, compassion, and social responsibility. Integrating Puritan values into Jakarta’s family life could help reshape the urban social and moral landscape, with churches and families working together to create a supportive and spiritually grounded society.